The Lateral Malleolus Is a Simple and Reliable Landmark that Can Be Used to Reliably Perform Restricted Kinematically Aligned Total Knee Arthroplasty—Anatomical and Clinical Studies in Japanese Population - Hiranaka, Takafumi; Jackson, William F. M.; Fujishiro, Takaaki; Suda, Yoshihito; Araki, Shotaro; Kamenaga, Tomoyuki; Koide, Motoki; Okamoto, Koji (The Journal of Knee Surgery, 2022)
In restricted kinematic alignment total knee arthroplasty (TKA), bone resection is performed within a safe range to help protect against failure from extreme alignments. Patient-specific instrumentation, navigations, and robotics are often required for restricting bone cuts within a specified safe zone. We hypothesized that the lateral malleolus could be used as a landmark for restricting the tibial osteotomy using a mechanical jig. Here, we examine its feasibility in anatomical and clinical settings. We studied long-leg standing radiographs of 114 consecutive patients (228 knees) who underwent knee arthroplasty in our institution. We measured the lateral malleolus angle (LMA), the angle between the tibial axis and the line between the center of the knee and the lateral surface of the lateral malleolus. The medial proximal tibial angle was also measured before and after restricted kinematic alignment TKA under restriction with reference to the lateral malleolus. Mean LMA was 5.5 ± 0.5 degrees. This was relatively consistent and independent of patient's height, weight, and body mass index. The lateral malleolus is a reliable bone landmark that can be used to recognize approximately 5.5 degrees of varus intraoperatively. A surgeon can use this as a restriction of the tibial varus cut up to 6 degrees without the requirement for expensive assistive technologies.
Keywords: knee; arthroplasty; kinematic; alignment; tibial axis; bony landmark